Hearing Outcome of Stapes Surgery in NIENT, Bangladesh (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: The aim of this study was to evaluate hearing outcome after stapedotomy in patients with Otosclerosis.Methods: This cross sectional study was carried out from July 2017 to January 2019 in National Institute of ENT, Unit V. About 22 patients with Otosclerosis were included in this study. Diagnosis of Otosclerosis was based on the history, medical status with Otoscopy, Tuning fork tests and Audiometric tests. We compiled data on the pre and post operative air-bone gap (ABG) at 0.5, 1, 2 KHZ. The ABG was Calculated using AC and BC thresholds on the same audiogram. Post operative hearing gain was then Calculated from the ABG before the operation minus the ABG of the last follow up examinationResults: In this study most of the cases were age group 14-30 years (72.7%), female (54.5%). Most common symptoms was progressive hearing loss, tinnitus (77.8%).The average preoperative hearing loss in this study was (AC) was 48.31±7.68. The average post opt. hearing (AC) at follow up was 28.95±10.30 with an average hearing gain of 15.40±8.53 dB which was significant. The average pre-operative ABG was 28.99 dB ± 8.10. The average post opt. ABG was analyzed at 1 follow up showed ABG 13.18±8.09 dB which was found to be significant.Conclusion: Stapedotomy is an effective surgical procedure for the treatment of otosclerosis which leads to improvement in patient’s quality of life. A favorable hearing outcome can be obtained by the combination of experienced hands with minimal surgical trauma and appropriate surgical technique.Bangladesh J Otorhinolaryngol; April 2020; 26(1): 31-36